2007
DOI: 10.1143/jjap.46.l448
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation Effects on Chemical Activity of Defects in Excimer-Laser-Annealed Polycrystalline Silicon Thin Films

Abstract: We irradiated H 2 and O 2 plasmas onto fluorinated Al 2 O 3 , which was prepared by exposing a virgin Al 2 O 3 sample to an SF 6 /O 2 plasma. The effects of the H 2 plasma irradiation were the reduction of the AlO x F y (x þ y ¼ 1:5) and AlF x (x < 3) bonding components and the realization of smooth sample surface. It was observed that the irradiation of the H 2 plasma induced Al-OH bonding. The Al-OH bonding was removed by the sequential irradiation of the O 2 plasma after the H 2 plasma irradiation. The O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…2(a Consistent results have been obtained in previous reports. 8) Therefore, the reproducibility of the above described results was confirmed. Thus, it was deduced that the electrochemical activity of GB is apparently reduced by hydrogenation.…”
Section: Effects Of Hydrogenation On Chemical Etchingsupporting
confidence: 55%
See 1 more Smart Citation
“…2(a Consistent results have been obtained in previous reports. 8) Therefore, the reproducibility of the above described results was confirmed. Thus, it was deduced that the electrochemical activity of GB is apparently reduced by hydrogenation.…”
Section: Effects Of Hydrogenation On Chemical Etchingsupporting
confidence: 55%
“…We have previously reported that the hydrogenation of ELA poly-Si suppresses chemical etching at GB, where Raman spectroscopy was used to detect stress reflecting the progress of etching at the film/underlayer interface. 8) It is expected that a more detailed analysis of chemical etching will be useful for characterizing the electronic activity of defects. Moreover, hydrogenation might assist in the observation of defects hidden by a high density of GBs.…”
Section: Introductionmentioning
confidence: 99%
“…We studied defects in excimer-laser crystallized poly-Si (Kitahara et al, 2007(Kitahara et al, , 2009a. We irradiated a-Si films (50 nm thick) on SiO 2 -coated fused quartz substrates with a XeCl excimer laser with 95% overlap.…”
Section: Excimer-laser Crystallizationmentioning
confidence: 99%
“…7) The enhancement of the etching rate at defects was related to electron-hole recombination centers in the band gap of Si. [8][9][10] We previously reported that the hydrogenation of ELA poly-Si suppresses the etching at GBs, 11,12) which is attributed to the passivation of dangling bonds (DBs) by hydrogen. It was also found that a high density of active defects exists in grains.…”
Section: Introductionmentioning
confidence: 99%